Consumer perception of product-service systems: Depicting sector-specific barriers in the mobility, clothing and tooling sectors - Muylaert, Coralie; Thiry, Géraldine; Roman, Philippe; Ruwet, Coline; De Hoe, Roxane; Maréchal, Kevin (Frontiers in Environmental Science, 2022)
The viability of PSS models is jeopardized by their low consumer attraction and retention. Using Social Practice Theory (SPT) and the habitual practice approach, this paper posits that barriers to consumer adoption and retention of PSS offers are twofold: (1) generic to the PSS offers and (2) sector specific. To approach and differentiate between generic and sector-specific barriers, the barriers in three different areas of PSS were analysed and compared: mobility, clothing and tooling. A quantitative and qualitative mixed methodology was convened with consumers in the Brussels Region (Belgium). We first demonstrate that the weight of the barriers to PSS adoption is related – to a certain extent – to the habitual practices associated to a particular sector. Second, we discuss the fact that the type of payment (pay-per-use or subscription) and the related consumer engagement (requiring a change in established practice or not) also have an impact on the perception and adoption of PSS offers by consumers.